Nutritional factors influencing microbiota-mediated colonization resistance of the oral cavity: A literature review - Akimbekov, Nuraly S.; Digel, Ilya; Yerezhepov, Adil Y.; Shardarbek, Raiymbek S.; Wu, Xia; Zha, Jian (Frontiers in Nutrition, 2022)
The oral cavity is a key biocenosis for many distinct microbial communities that interact with both the external environment and internal body systems. The oral microbiota is a vital part of the human microbiome. It has been developed through mutual interactions among the environment, host physiological state, and microbial community composition. Indigenous microbiota of the oral cavity is one of the factors that prevent adhesion and invasion of pathogens on the mucous membrane, i.e., the development of the infectious process and thereby participating in the implementation of one of the mechanisms of local immunity – colonization resistance. The balance between bacterial symbiosis, microbial virulence, and host resistance ensures the integrity of the oral cavity. In this review, we have tried to address how nutritional factors influence the integrity of the oral indigenous microbiota and its involvement in colonization resistance.